2011
DOI: 10.4269/ajtmh.2011.11-0363
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Fever Vaccine Seroconversion in Travelers

Abstract: To assess immunity after yellow fever (YF) 17D live-attenuated vaccination, we measured the antibody levels before vaccination and at 21 days and 8 months after vaccination in YF-naïve travelers. Thirty subjects were enrolled in the study, with 100% providing sera at 21 days and 86.6% providing sera at 8 months. All subjects seroconverted by day 21, and the geometric mean titers of the anti-YF antibodies decreased between day 21 and month 8 from 6,451 to 1,246. This study corroborates the high rates of serocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
7
0
3
Order By: Relevance
“…As can be seen, the difference of values in Figures 1 and 2 occurs not only between simulated and experimental data, but also in the results of distinct studies, see, [41][42] and among individuals in the same study. This is an implicit characteristic of biological experiments.…”
Section: Computational Resultsmentioning
confidence: 78%
“…As can be seen, the difference of values in Figures 1 and 2 occurs not only between simulated and experimental data, but also in the results of distinct studies, see, [41][42] and among individuals in the same study. This is an implicit characteristic of biological experiments.…”
Section: Computational Resultsmentioning
confidence: 78%
“…Probably, this was due to multiple exposures and/or vaccinations. No indicative data were confirmed, because no consensus was found in the literature regarding the higher titers shown by Caucasians than by Blacks and Hispanics, as well as by men than by women 20,[22][23][24] . In a Brazilian study, a lower seroconversion rate was observed on antibody levels after vaccination against yellow fever in 12-month-old children who simultaneously received the triple viral vaccine than in those who received the 30-day interval vaccination.…”
Section: Discussionmentioning
confidence: 79%
“…There is no consensus on the titration conferring immunity. However, the values used as positive, i.e., values more than 10 are well accepted in the literature 10,11,19,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Schwartz et al, identified high rates of cross-reactivity in the anti-DENV Panbio IgG ELISA when the patients were previously vaccinated against YF and JE, overestimating past DENV exposure when using this assay (16). Antibody cross-reactivity may depend on the time frame of vaccination in the context of testing for anti-DENV IgG (17).…”
Section: Discussionmentioning
confidence: 99%